Proteomic properties of Salmonella isolates - N. B. Shadrova; O. V. Pruntova; G. S. Skitovich (Ветеринария сегодня)
The paper presents results of Salmonella of studying Salmonella isolate properties by MALDI-TOF method using MALDI Autoflex III mass-spectrometer. Microorganism identification was performed using direct loading method followed by comparison of mass spectra with the database set in the apparatus. Peaks typical of many Enterobacteriaceae representatives and mass to charge ratio (m/z), characterizing Salmonella were determined.